Evaluation of carbon aerogel-based solid-phase extraction sorbent for the analysis of sulfur mustard degradation products in environmental water samples. (May 2018) - Jõul, Piia; Vaher, Merike; Kuhtinskaja, Maria
Abstract: In this study, SPE method using a carbon aerogel(CA)-based sorbent was developed and evaluated for the simultaneous extraction of sulfur mustard (HD) degradation products from environmental water samples. Applied CAs proved to be very promising materials for use as SPE sorbents, due to their high porosity, very low density and a large specific surface area. 10 degradation products of HD, both aliphatic and cyclic (thiodiglycol (TDG), TDG sulfoxide, TDG sulfone, 3, 5-dithia-1, 7-heptanediol, 3, 6-dithia-1, 8-octanediol, 1, 4-thioxane, 1, 3-dithiolane, 1, 4-dithiane, 1, 2, 5-trithiepane, and 1, 4, 5-oxadithiepane) were extracted on a CA-based SPE cartridge. The concentrations of target analytes in the eluate were determined by HPLC-DAD and CE-DAD. Several parameters affecting the extraction efficiency, including the kind and volume of the eluting solvent, sample loading flow rate, volume and ionic strength as well as the reusability of the cartridge, were investigated and optimized to achieve the best performance for the analytes. A series of quantitative parameters such as linear range, coefficient of determination, LOD, LOQ and precision were examined under the optimized conditions. High sensitivity (LODs 0.17–0.50 μM) and high precision (intraday RSD = 2.0–7.7% and interday RSD = 2.7–9.9%) for all the analytes were achieved. The performance of the CA-based sorbent was compared with that of commonly used SPE sorbents. Applied for the analysis of spiked pore water samples collected from the Bornholm Basin, one of the largest chemical warfare dumping sites in the Baltic Sea, the proposed method allowed high SPE recoveries of all the analytes ranging from 83.5 to 99.7% to be obtained. Graphical abstract: Highlights: A method was developed for extraction of 10 degradation products of sulfur mustard. Carbon aerogel-based sorbent was evaluated for extraction of target compounds. The obtained recoveries were at least 80%. Applied for analysis of target compound in environmental water samples.